Strengthening the Pancasila Student Profile through Social Studies Learning in Elementary Schools - Saqjuddin Saqjuddin (FKIP UNSULTRA, 2025)
The Pancasila Student Profile represents the ideal characteristics of Indonesian learners who possess global competencies and behave in accordance with the values of Pancasila. In the context of Elementary Schools (SD), Social Studies (IPS) learning plays a strategic role in instilling values of nationalism, social responsibility, and culture that contribute to the formation of the Pancasila Student Profile. This study aims to theoretically examine how Social Studies learning in elementary schools can effectively strengthen the six dimensions of the Pancasila Student Profile, namely faith and devotion to God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity. This research employs a literature review method by analyzing various national and international journals, books, and relevant curriculum documents, particularly those related to the Merdeka Curriculum. The findings suggest that contextual Social Studies learning, project-based learning, and the integration of local and global values can effectively serve as a medium for cultivating the character and competencies of the Pancasila Student Profile. Teachers play a crucial role in designing learning experiences that encourage students to think critically, collaborate, and reflect on the values of Pancasila in real-life situations. Ongoing training and support for teachers are necessary to develop transformative and humanistic learning practices. Therefore, strengthening the Pancasila Student Profile through Social Studies learning is not only possible but also essential in preparing Indonesia's Golden Generation of 2045.